(untitled) (Journal of Preventive and Social Medicine, 2025)
Background: District Health Information Software 2 (DHIS2) is an open source, web-based, health management information system (HMIS) recognized as world’s largest HMIS platform, customized for health information system of Bangladesh for decentralized data entry since 2011. Health care managers and employees should be well informed about the health information system for accurate, appropriate, precise, timely, valid information and also interpretation of information which are the basis for policy planning and decision-making at various levels of the organization. The study aimed at exploring the limitations of DHIS2 in decision making process for health service management among the Upazila (Sub district) level health managers of Bangladesh. Methods: The cross sectional study was conducted among the Upazila Health and Family Planning Officers (UH&FPOs) of Bangladesh during the period of January to December 2018. All (482) UH&FPOs of Bangladesh posted as regular, current charge or in-charge were included for the study. Data were collected by a pre-tested semi-structured email-based questionnaire. Results: Response rate was 88.8% (428 out of 482). The mean age of the respondents was 47.08 (±6.33 SD). Mean duration of job experiences as UH&FPO was 1.9 years (±1.635 SD). Regarding limitation, the study revealed that 76.2% (of 424) UH&FPOs think that lack of rrealizing the Importance of DHIS2 by Doctors, Nurses and other Staffs is the most important “Facility Centered Barriers” for using DHIS2 as a decision support tool of Upazila health service management. Beside this 71.2% UH&FPOs think that lack of effective training of the staffs concerned with DHIS2 operation are the second most important barrier. The study also revealed that 59.7% (of 402) UH&FPOs think that absence of the option for automatically displaying the summary reports of various datasets in the respective Upazila dashboard is the most important “Software Centered Barriers” for using DHIS2 as a decision support tool of Upazila health service management beside this 58.5% UH&FPOs think difficulties in identifying the management related data elements from various data sets of DHIS2. Conclusion: So, this study recommends scaling up DHIS2 by redesigning training programs with more focus on the ways of its’ application in the decision making process, create awareness among all categories of health staffs, customization of its contents and more research on this ground. These initiatives will explore several innovative approaches to monitor health indicators by DHIS2, measure and plan health interventions to ensure quality health service and will lead towards achieving Sustainable Development Goal 3 (SDG-3). JOPSOM 2023; 42(2): 43-50